Study on the microbial diversity of ear canal secretions from patients with otomycosis - Chen, Zhuxiang; Zhao, Zhang (Frontiers in Surgery, 2024)
Otomycosis is caused by fungi, which usually cause discharge and additional discomfort. The highest incidence of otomycosis occurs in summer. To better treat this disease, it is necessary to study the microbial diversity of otomycosis secretions. In this regard, this study used high-throughput sequencing technology to determine the microbial diversity of the ear canal secretions of six typical patients with otomycosis in Wuhan via internal transcribed spacer (ITS) and 16S rRNA analyses and proposed a reasonable clinical treatment plan. Six patients with otomycosis in the Department of Otorhinolaryngology, Hubei Third People's Hospital Affiliated with Jianghan University, were selected from June 2022 to August 2022. The results showed that Staphylococcus spp. (average abundance 29.05%) was the dominant bacteria and Aspergillus spp. (average abundance 90.68%) was the dominant fungus involved in otomycosis secretion. Aspergillus spp. can cause inflammation of the external auditory canal combined with bacterial infections such as Staphylococcus spp., which can cause discharge in the ear canal. High-throughput sequencing provides comprehensive information on the microbial community involved in otomycosis discharge and will aid in evaluating the efficacy of clinical treatment and medication.